Association Between Road Traffic Accidents and Economic Growth with a Special Focus on Alcohol Consumption – A Comparison of Six Alpine Countries - Klára BORUZS; Róbert BODA; Gábor BÁNYAI; Viktor DOMBRÁDI; Gergő József SZŐLLŐSI; Klára BÍRÓ (SEA: Practical Application of Science)
By preventing traffic accidents, the economic burden on health care can be reduced. The aim of our research was to examine the relationship between road traffic accidents with injuries and changes in the number of passenger cars per thousand inhabitants with regard to economic development and alcohol consumption in the Alpine region. A study on the ecological relationships was conducted for the Alpine countries that had data going back at least 20 years. Spearman's rank correlations were used for analysis. Road traffic accidents involving injuries were significantly and negatively correlated with years, Gross domestic product and cars per thousand inhabitants. A significant positive correlation was found between road traffic accidents and alcohol consumption. In conclusion, an increase in the number of cars in itself does not lead to more accidents and avoidable deaths in any country. Therefore, policy makers should consider investigating the introduction of zero tolerance in these countries.